Controllable cell manipulation in a microfluidic pipette-tip design using capacitive coupling of electric fields. Issue 23 (31st October 2019) - Wimberger, Terje; Peham, Johannes R.; Ehmoser, Eva-Kathrin; Wassermann, Klemens J.
Abstract : Capacitive coupling of electric fields diminishes energy dissipation and offers superior control over field parameters, resulting in predictable biological outcomes. Abstract : Systems designed toward cell manipulation by electric fields are inherently challenged by energy dissipation along the electrode–electrolyte interface. A promising remedy is the introduction of high- k electrode passivation, enabling efficient capacitive coupling of electric fields into biological samples. We present the implementation of this strategy in a reusable pipette tip design featuring a 10 μl chamber volume for life science applications. Prototype validation and comparison to conductive gold-coated electrodes reveal a consistent and controllable biological effect that significantly increases the reproducibility of lysis events. The system provides precise descriptions of HEK-293 lysis dependency to variables such as field strength, frequency, and conductivity. Over 80% of cells were reversibly electroporated with minimal electrical lysis over a broad range of field settings. Successful transfection requires exponential decay pulses and showcases how modulating capacitive coupling can advance our understanding of fundamental mechanics in the field of electroporation.